Design of a Mobile Application for Real-Time Flood Information in North Aceh Region Based on GIS and Haversine Method (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This research focuses on the design and development of a mobile application for real-time flood information in the Aceh Utara region, utilizing Geographic Information Systems (GIS) and the Haversine method. The primary goal of this study is to provide an accessible and reliable tool for residents and local authorities to monitor flood events, allowing them to make timely and informed decisions. By integrating GIS technology, the application enables users to view flood-prone areas on an interactive map and receive real-time alerts based on proximity to flood locations. The Haversine method is applied to calculate distances between various flood points and user locations, ensuring the accuracy of the alerts. The methodology includes the design of a user-friendly interface and the implementation of real-time data processing. Results show that the application successfully integrates GIS and the Haversine method, providing accurate flood data and enhancing user experience in disaster management. The significance of this research lies in its potential to improve disaster preparedness and response in flood-prone regions, thus reducing the impact of floods on communities and infrastructure. This mobile application can be a crucial tool for managing flood risks and ensuring the safety of the population in Aceh Utara.